The Protective Effect of Astragalus Polysaccharide on Experimental Autoimmune Encephalomyelitis in Mice by Activating the AMPK/JAK/ STAT3/Arginase-1 Signaling Pathway - Wang, Jin-Li; Li, Bin; He, Xue-Xin; Gao, Chang-Yu; Wang, Jue-Qiong; Guo, Ruo-Yi; Fan, Jing-Yi; Zhang, Ya-Nan; Quan, Mo-Yuan; Song, Shuang; Xie, Tao (Current Pharmaceutical Biotechnology, 2025)
ObjectiveThis study aimed to investigate the protective effect and mechanism of Astragalus polysaccharide (APS) on autoimmune encephalomyelitis.MethodsC57BL/6 mice were randomly divided into the blank control group, EAE group, and APS intervention group (n=15/group). The Experimental Autoimmune Encephalomyelitis (EAE) mouse model was established by active immunization. The pathological changes in the spinal cord were evaluated by Hematoxylin-eosin (HE) and Luxol Fast Blue (LFB) staining. The number of CD11b+ Gr-1+ myeloid-derived suppressor cells (MDSCs) in the spleen tissues of mice in each group was determined by immunofluorescence staining. The expression of Arginase-1 in the spinal cord and spleen of each group was detected by immunofluorescence double staining. The TNF-α, IL-6, and Arginase-1 levels in the spleen were detected by ELISA assay. A western blot was used to detect the protein expression of the AMPK/JAK/STAT3/Arginase-1 signaling pathway.ResultsAfter the intervention of APS, the incidence of autoimmune encephalomyelitis in mice of the APS group was significantly lower than that in the EAE group, and the intervention of APS could significantly delay the onset time in the EAE mice, and the score of neurological function deficit in mice was significantly lower than that in EAE group (P < 0.05). APS intervention could reduce myelin loss and improve the inflammatory response of EAE mice. Moreover, it could induce the expression of CD11b+ GR-1 + bone MDSCs in the spleen and increase the expression of Arginase-1 in the spinal cord and spleen. This study further demonstrated that APS can protect EAE mice by activating the AMPK/JAK/STAT3/Arginase-1 signaling pathway.ConclusionAfter the intervention of APS, myelin loss and inflammatory response of EAE mice were effectively controlled. APS promoted the secretion of Arginase-1 by activating MDSCs and inhibited CD4+T cells by activating AMPK/JAK/STAT3/Arginase-1 signaling pathway, thus improving the clinical symptoms and disease progression of EAE mice.
Keywords: AMPK